Identifying the Validity and Reliability of a Self-Report Motivation Instrument for Health-Promoting Lifestyles Among Emerging Adults - An, Min; Zhang, Xiao (Frontiers in Psychology, 2018)
Objective: Studies on the effectiveness of health-promoting programs across educational contexts need a new tool for measuring health motivation. This study aims to develop a new health motivation questionnaire, namely the College Students’ Health Motivation Questionnaire (CSHM-Q), for college students. Design: An original item pool of the CSHM-Q was developed based on a systematic synthesis and review of related instruments and the content analysis of focus group interviews (N = 93). The instrument was then validated using a sample of 205 college students. Setting: Interviews and survey were conducted at three universities in China. Methods: This study explores the content validity, construct validity, and reliability of a self-report motivation instrument based on the framework of Self-Determination Theory. Results: A pilot study showed satisfactory content validity of the motivation constructs and produced 40 items for the CSHM-Q. Results of exploratory factor analysis and parallel analysis further substantiated a three-factor structure of the CSHM-Q. The finalized CSHM-Q has 21 items. Conclusion: Given adequate psychometric properties, the CSHM-Q is a promising measurement tool of health motivation for practical and research purposes.